Investigating the effect of neighboring buildings’ orientation and the passage on the amount of energy consumption (case example: common residential buildings in Tehran) - Meysam Zekavat; Mansoure Tahbaz; Mohammad Reza Hafezi (تحقیقات کاربردی علوم جغرافیایی)
Buildings are the primary consumers of energy in the country, accounting for approximately 30-50% of total energy consumption. In our country, around 33% of energy is allocated to residential, commercial, and public buildings. The objective of this study is to examine the impact of a building's orientation on its energy consumption. The research is focused on the common 4 and 5-story residential buildings in District 5 of Tehran, specifically on Ferdous Sharq Blvd. The research adopts a descriptive-analytical methodology based on both organizational and field data collection. Six similar residential blocks in different lighting positions were selected to gather data. These blocks share identical characteristics in terms of land area, infrastructure area, number of floors, heating and cooling systems, and other factors. The only distinction among them is their location within a passage. Subsequently, Design Builder software was employed to simulate and compare their energy consumption. The findings of the research reveal that the average energy consumption, with a precision of 98%, for the northern blocks is 7,261 kilowatt hours per square meter per year, while for the southern blocks it is 11,247 kilowatt hours per square meter per year, and for the overall blocks it is 5,254 kilowatt hours per square meter per year. This is approximately three times the ideal building's energy consumption. The northern blocks consume about 5% more energy than the southern blocks. A block that receives light from three sides (north, south, and west) consumes about 11% more energy than the average, whereas a block that receives light from two sides (north and south) consumes about 5% less energy than the average. The north blocks have an energy label of D, whereas the south blocks, except for the end block that receives light from three sides (north, south, and west), have an energy label of C. Consequently, the south blocks generally demonstrate better energy consumption performance.